2020
DOI: 10.1111/papr.12874
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Efficacy and Safety of Local Infiltration of Tramadol in Pediatric Tonsillectomy Pain: A Systematic Review and Meta‐Analysis

Abstract: Objectives The aim of this systematic review and meta‐analysis was to appraise clinical evidence of the impact of peritonsillar infiltration of tramadol, on postoperative pain control and the occurrence of adverse effects in children undergoing tonsillectomy. Methods A database search was conducted to identify randomized controlled trials (RCTs) pertinent to peritonsillar infiltration of tramadol compared to no treatment (placebo) or other analgesic regimens. The outcomes of interest were postoperative pain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…[31][32][33][34] In the previous meta-analyses, the effect of peritonsillar applied tramadol on postoperative pain relief was investigated. 9,35,36 However, unlike in these studies, in our current study, peritonsillar applied topical tramadol was compared simultaneously with placebo or other drugs infiltrated to tonsil bed. In addition, subgroup analysis by time after pediatric adenotonsillectomy was done.…”
Section: Discussionmentioning
confidence: 98%
“…[31][32][33][34] In the previous meta-analyses, the effect of peritonsillar applied tramadol on postoperative pain relief was investigated. 9,35,36 However, unlike in these studies, in our current study, peritonsillar applied topical tramadol was compared simultaneously with placebo or other drugs infiltrated to tonsil bed. In addition, subgroup analysis by time after pediatric adenotonsillectomy was done.…”
Section: Discussionmentioning
confidence: 98%
“…The adverse effects of tramadol have been evaluated in other systematic reviews and meta-analyses. Tsaousi et al, 2020 found a negligible association of adverse effects after local administration of tramadol in children undergoing tonsillectomy [ 53 ]. In this sense, Mattar et al, 2019, carried out the evaluation of analgesia and adverse effects of tramadol during a diagnostic outpatient’s hysteroscopy and reported that the pooled analysis showed no increase in the risk of minor adverse effects, such as nausea, vomiting, and bradycardia [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…20 Georgia Georgia GG Georgia G et al concluded that peritonsillar infiltration of tramadol resulted in significant reduction in post tonsillectomy pain intensity up to 24 hours. 21 Tugce Simsek et al compared the trans mucosal application in nasal packing infiltrated with tramadol, Lidocaine and saline. They suggested that patients in tramadol group were most satisfied and required least additional analgesics compared with Lidocaine and saline group.…”
Section: Discussionmentioning
confidence: 99%